PENGARUH PERTUMBUHAN EKONOMI DAERAH PADA DAYA SAING DENGAN KESERASIAN BELANJA DAERAH, KEMANDIRIAN KEUANGAN DAERAH SEBAGAI VARIABEL PEMODERASI - Tonu, Daniel; Badera, I Dewa Nyoman; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.01.TAHUN 2015, 2015)
COMPETITIVENESS WITH HARMONY EXPENDITURE, THE REGIONAL FINANCIAL INDEPENDENCE AS A MODERATING  This study aims to determine the Effects of regional Economic Growth to the Competitiveness with Harmony Expenditure, The Regional Financial Independence As a moderating. The research location is in the main Statistics Office of NTT and the General Directorate of Balance Fiscal Web site in Regional Office. The object which is used in this study is the scope of the Regional Competitiveness government district/city in the province of East Nusa Tenggara, in the range of year 2007 until 2012, using the secondary data. The method of data collection is using the non-participation observation, with sampling technique using purposive sampling. The data analysis technique used is Moderated Regression Analysis (MRA) which is a special application of multiple linear regression in regression equation contains elements of interaction (multiplication of two or more independent variables). The results showed that (1) The regional economic growth, Harmony Expenditure and Financial Independence area simultaneously effect on positive and significant Competitiveness. (2) The economic growth gives a negative effect significantly on the competitiveness. (3) The compatibility shopping area turns to negative effect and it is not significant on the competitiveness. (4) The independence of financial area turns to negative effect and it does not show a significant result on competitiveness. (5) The increasing of shopping area compatibility will strongly influence the regional economic growth and result a positive effect on the competitiveness of the region. (6) The Higher Regional Financial Independence improve the moderating of economic growth influence which positively impact but it does not show a significant effect on the Regional Competitiveness, and (7) the high level in regional financial independence increases the negative influence on it, but it is not significant to economic growth competitive
Keywords: Economic Growth, Harmony Expenditure, Financial Independence, Regional Consumption per Capita.